Interaction of tumor and stromal cells in pancreatic cancer - Gaedcke, Jochen; König, Alexander (Translational Cancer Research, 2017)
Aberrant cell signaling is a hallmark of cancer. This led to an extensive research and the identification of several oncogene driven signaling pathways (cell-autonomous). However, solid tumors are not only composed of cancer cells but also of normal cells such as fibroblasts, endothelial cells or immune cells. In particular, pancreatic cancer is one of the preeminent examples of a cancer with an excessive stroma reaction. In some cases cancer cells represent only 10% of the entire tumor. It is an ongoing discussion whether this stroma reaction is friend or foe to the hosting organism (1-3).